TVET Programs in Nepal: Issue of Access and Relevancy - Sharma Neupane, Manoj (Journal of Training and Development, 2020)
Equitable access of market relevant TVET (Technical and Vocational Education and Training) programs is the first and foremost pre-condition to get the desired outcomes from TVET. The access and relevancy of TVET programs in Nepal are usually questionable. The major objectives of this paper is to analyze the access and relevancy of presently available long term TVET programs and identify its gap with the market demand. The analytical approach adopted for this paper is mainly quantitative and is based on the analysis of micro data of TVET institutes affiliated with Council for Technical Education and Vocational Training (CTEVT) and Central for Education and Human Resource Development (CEHRD) with corresponding information of their location, programs and enrolment capacity. Likewise, review of various other literatures including, journal articles, workshops proceedings, research reports etc. are also taken into reference. Significant variation is found between the ratio of district level enrolment capacity of long-term TVET programs to corresponding number of SEE graduates of the districts which raises question on the equitable access of TVET programs in terms of geography. Based on the analysis made in this paper, health related programs are justified as over accessed programs whereas a clear gap can be observed in the supply mechanism of TVET regarding tourism and agriculture sector. Attention is therefore needed to promote TVET programs in agriculture and tourism related sectors both in quality and quantity in order to mitigate existing mismatch between demand and supply.